(untitled) (Nepal Medical College Journal, 2020)
Aneurysmal bone cyst (ABC) of the talus is an extremely rare lesion. Less than 20 cases have been reported in PubMed till 2012 and none from Nepal. We report a rare case of primary ABC of talus in a 17 year old male that was managed by extended intra-lesional curettage and autologous cancellous iliac crest bone grafting. The patient had excellent functional outcome and there was no recurrence at 1 year of follow-up.